2017
DOI: 10.18632/oncotarget.23002
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates myocardial ischemia-reperfusion injury

Abstract: BackgroundCardiovascular diseases (CVDs) are at a badly high-risk of morbidity and mortality in the world.MethodsOur study was attempted to investigate the cardioprotective role of curcumin. Hearts injury was assessed in isolated hearts and the rats of coronary artery ligated.Results and ConclusionsThe inhibition of pro-inflammatory cytokines was observed by curcumin in coronary artery ligated rats. ST segment was also reduced by curcumin. Triphenyltetrazolium chloride staining (TTC) staining and pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 17 publications
4
31
0
Order By: Relevance
“…Curcumin improved dyslipidemia and liver dysfunction in high fat high sucrose fed rats 15 . Curcumin has the ability to alleviate myocardial injury with inhibition of pro-inflammatory cytokine in rats with coronary artery ligated and in isolated heart 64 which was likely demonstrated in the present study. Modulation of post-translational modifications like protein acetylation is considered as one of the most recent strategy to combat cardiovascular disease; curcumin and DHA are emerging agents that possess this activity mediated through modulation of sirtuin 65 .…”
Section: Discussionsupporting
confidence: 73%
“…Curcumin improved dyslipidemia and liver dysfunction in high fat high sucrose fed rats 15 . Curcumin has the ability to alleviate myocardial injury with inhibition of pro-inflammatory cytokine in rats with coronary artery ligated and in isolated heart 64 which was likely demonstrated in the present study. Modulation of post-translational modifications like protein acetylation is considered as one of the most recent strategy to combat cardiovascular disease; curcumin and DHA are emerging agents that possess this activity mediated through modulation of sirtuin 65 .…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that curcumin is a potent cardioprotective compound, which may have beneficial effects on MIRI by reducing oxidative stress, preventing inflammation and inhibiting cardiomyocyte apoptosis (16). Numerous studies have indicated that traditional Chinese medicine (TCM) exerts a potent cardioprotective effect on MIRI and may be used as a therapeutic approach for its treatment (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…At present, it is not known how simvastatin can protect the myocardium by reducing the expression of caspase-3 through anti-apoptosis. However, Liu et al (20) indicated that the expression of p53 and caspase-3 in simvastatin decreased significantly in the the simvastatin group with simvastatin preconditioning renal ischemia reperfusion, and the level of oxygen free radicals were also decreased (P<0.05). It is presumed that simvastatin may scavenge the excess oxygen free radicals induced by renal ischemia-reperfusion injury, and then decrease the oxidative damage effect of myocardial cells, reduce the expression of p53 and caspase-3, and ultimately inhibit cell apoptosis.…”
Section: Discussionmentioning
confidence: 97%